Near infrared spectroscopy: a method for the monitoring and management of the commercial exploitation of the brown mussel (Perna perna) in southeastern Brazil - de Oliveira, Amanda Gleyce Lima; Valladares, Vanessa; Santos, Cláudia Portes; Mello-Silva, Clélia Christina (Frontiers in Marine Science, 2023)
Perna perna (Linnaeus, 1758) is one of the most commercialized mollusk species in Brazil. The individuals with a shell length of at least 50 mm are considered to be adults and suitable for commercialization and human consumption. However, the lack of control over the size of extracted mussels is a recurrent and worrisome issue, which may compromise the long-term survival of natural stocks. The present study evaluated the potential to differentiate juvenile brown mussels from adult individuals by using Near Infrared Spectroscopy (NIRS). A total of 176 mussels were obtained from Jurujuba and Vermelha beaches, both located in Guanabara Bay, in the state of Rio de Janeiro, Brazil. Spectra were obtained from the muscle group and a specific part of the shell, with the specimens being separated by size (shell length < 50 mm or > 50 mm), following the current Brazilian legislation. The classification of the muscles by mussel size obtained a hit rate of 66.03%, while the hit rate of the shells was 78%. The two groups were also distinguished efficiently when the two localities were analyzed separately. The results reflect the influence of environmental factors on the chemical composition of the P. perna adults from different areas, with a 85.71% hit rate. The results indicate that NIRS is a potentially effective diagnostic tool for the monitoring and management of the commercial exploitation of natural P. perna stocks.